Learning and Teaching about Holocaust: Teacher Education Students' Perspective in Serbia - Snežana Z. Štrangarić; Мila B. Beljanski; Dejan M. Dorđić (University of Belgrade, Teacher Education Faculty, 2023)
Holocaust, defined as the process of suffering of 6 million Jews, organized by the Nazi Germany during the World War II, is a topic that does not lose its relevance. Teaching about the Holocaust should be aimed at students' understanding of historical facts, and it is also necessary to point out the importance that this part of the past has for the modern world and current social problems. In the teaching process, attention should be paid to preserving the memory of the lives of the Jews and the Jewish community in Europe before the war in order to highlight their rich cultural heritage. The paper presents the results of an empirical research aimed at analyzing the challenges in the process of learning and teaching about the Holocaust in formal and informal education. Using a close-ended questionnaire, the perspective of the students of teacher education faculties in Serbia was investigated, and the sample included 741 respondents. The results indicate a varied understanding of the term Holocaust, with the prevailing understanding that the process included a wide range of victims. Students find this topic emotionally taxing and very disturbing, and they identify this as one of the biggest obstacles encountered in teaching about the Holocaust. The obtained results can serve as a platform for creating implications for educational policies and formulating recommendations for the improvement of the school practice with the aim of deepening and expanding knowledge on this topic, but also with the aim of developing intercultural competences, reflective dealing with stereotypes and prejudices, and fostering a culture of remembrance.